Bioproducts and Homeopathy in Lasiodiplodia Rot (Lasiodiplodia sp.) Control and Development of Passion Fruit Seedlings - Trento, Rogelho Alexandre; Bonaldo, Solange Maria; Wobeto, Carmen; Zanuzo, Marcio Roggia; Agostini, Juliana da Silva; Ribeiro, Daniela (Journal of Agricultural Studies, 2021)
The aim of this study was to evaluate the effects of homeopathic medicine Calcarea carbonica 12CH and bioproducts: filtrates of saprobic fungi from Amazon, green propolis nosode 06CH, filtrate of Pichia sp., green propolis extract, Bacillus subtilis; to control Lasiodiplodia (Lasiodiplodia sp.) and development of passion fruit seedlings (Passiflora edulis Sims f. flavicarpa Degener). The experiment was carried out in a completely randomized design with 10 treatments in a parcel divided in time. Each plot consisted of 5 plants for analysis. Data were subjected to analysis of variance and when significant compared by Scott-Knott test (p> 0.05). Variables related to plant growth and the area under the disease progress curve (AUDPC) were evaluated. Assessments were performed at 67, 74 and 82 days after transplantation. There was no reduction in AUDPC for treatments compared to control. As for plant height (cm), the best treatments were Pichia sp. and Gonytrichum sp. with an increase in relation to control of 29.70% and 18.24%, respectively, and increased leaf area (cm2) by 27.42% and 19.85%, respectively. B. subtilis, Pichia sp. and Gonytrichum sp., increased total biomass by 42.31%, 32.82% and 21.44%, respectively. The filtrates application from Pichia sp., Filtrate from Gonytrichum sp., C. carbonica 12CH and B. subtilis provided better performance in the development of passion fruit plants with an increase in the main morphological attributes. The results show that the use of bio products improves the development of seedlings, especially the use of yeast and saprophytic fungi by controlling the biochemical and physiological processes of plants during development.